(Re-)invented Chan Lineage, Unique Vietnamese Meditation School, or Both? Thích Thanh Từ’s “Revived” Trúc Lâm Tradition of Thiền Tông - Nguyen, Trang T. D. (Religions, 2024)
This study explores how images of the past have been deployed to set up current arrangements of leadership and institutional identity by considering the career and teachings of Thích Thanh Từ in connection with his “revived” Buddhist tradition in Vietnam. Promoted as a continuation of the unique and pure Vietnamese Buddhist meditation tradition and associated with the Vietnamese national identity, the contemporary Trúc Lâm (Bamboo Grove) is a pride of many Vietnamese Buddhists. The original Trúc Lâm is claimed to be founded by the heroic King-turned-monk Trần Nhân Tông in the thirteenth century. The tradition was supposedly transmitted through the next two generations and died out. In the twentieth century, a Southern Vietnamese monk, Thích Thanh Từ (1924–), who had quit Pure Land (Tịnh Độ, C. Jingtu淨土) Buddhism to self-learn and practice meditation, decided to reinvent the medieval Trúc Lâm tradition and became the founder of the contemporary Trúc Lâm. Despite growing up during French colonization and American war, Thanh Từ was not politically involved; instead, he focused on setting up new monasteries, taught meditation, and discouraged his followers from political and social engagement. This paper examines how successful Thích Thanh Từ and his disciples are in popularizing Trúc Lâm in Vietnam, given that the majority of Vietnamese Buddhists follow Pure Land devotional practices. More importantly, it describes how Thích Thanh Từ combines the teachings attributed to Trần Nhân Tông and two Chinese Chan masters, Huike慧可 (the Second Patriarch) and Huineng惠能 (the Sixth Patriarch), to form Trúc Lâm’s philosophical views and meditation techniques. With the clear-cut distinction between the delusional mind of sentient beings and the perfect mind of enlightened beings, Thích Thanh Từ presents the goal of Trúc Lâm practice as attaining the state of no-thought and sharpening it to perfection to perceive the “buddha nature” (phật tính, S. buddhadhātu, C. foxing 佛性) understood as the pure mind of nonduality and nonform. Outlining that process, he emphasizes the importance of “sudden awakening” (đốn ngộ, C. dunwu 頓悟) followed by “gradual cultivation” (tiệm tu, C. jianxiu 漸修). His meditation manual for ordinary practitioners with no experience of sudden awakening contains key techniques of (1) stabilizing the mind by counting and then observing breaths, (2) recognizing the “true mind” (chân tâm, C. zhenxin真心) through practicing “no abiding in thoughts” (biết vọng không theo), “no mind for the externals” (đối cảnh vô tâm), “no dualistic discrimination” (không kẹt hai bên), and then proceeding to the stage of permanently abiding in the nature of true mind. These meditation methods are pertinent to Trúc Lâm’s view that all phenomena that emerge via speculative thoughts are unreal and illusory, and that only the true mind is real. The first section of this paper explores historical connections between Vietnamese and Chinese forms of Buddhism, shedding light on why Trúc Lâm embraces Thiền Tông, which is transmitted from Chinese Chan zong, and how Thích Thanh Từ builds connections between Thiền Tông and the Vietnamese national identity. The second section focuses on Thích Thanh Từ’s own life story, on how he practiced meditation and suddenly experienced “unlearned wisdom” (trí vô sư/vô sư trí, C. wushi zhi無師智,an alternative term for true mind and buddha nature as a result of his practice) and how he succeeded in spreading the “revived” Trúc Lâm. With the first two sections as a background, in the third section, this paper explores Thích Thanh Từ’s views and practices and critically analyzes those views and practices in the conclusion. Overall, I argue that Thích Thanh Từ’s instructions on meditation are closely intertwined with his view of reality, which in turn is based on the mainstream Chan zong ideas.